Syncope and Hip Fracture Incidence Among the Elderly: Insiden Pingsan dan Patah Tulang Pinggul pada Lansia - Eneama, Wijdan Abbas; Naser , Rand Salah; Issa, Wafaa Abdulkadhim (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Syncope, a transient loss of consciousness due to reduced cerebral blood flow, is a common geriatric condition linked to falls and injury. Specific Background: In older adults, the combination of comorbidities, impaired balance, and bone fragility increases susceptibility to severe consequences such as hip fractures, which are associated with high morbidity and mortality. Knowledge Gap: While syncope is recognized as a fall risk factor, its direct relationship with hip fracture prevalence and fracture severity patterns in elderly populations remains underexplored. Aims: This study aimed to quantify hip fracture incidence among elderly patients with syncope, identify high-risk subgroups, and assess the influence of syncope characteristics on fracture severity. Results: In a cross-sectional study of 200 patients, 36% sustained fractures, including 16% hip fractures; prolonged syncope (>2 minutes), absence of warning signs, and recurrent episodes were strongly associated with severe injuries. Women aged 45–50 with balance disorders or chronic conditions were disproportionately affected. Novelty: The research delineates a duration–severity gradient for syncope-induced fractures and highlights modifiable clinical predictors. Implications: Targeted preventive strategies—such as syncope workups, balance rehabilitation, and bone health screening—may substantially reduce fracture-related disability and mortality in at-risk elderly populations.Highlight : Syncope is a major risk factor for injury in older adults. Hip fractures were found in 16% of syncope patients. The duration of syncope affects the severity of fractures. Keywords : Syncope In Elderly, Hip Fractures, Falls Related Injuries, Fracture Patterns, Risk Factors